FilGAP, a Rho/Rho-associated protein kinase–regulated GTPase-activating protein for Rac, controls tumor cell migration - Saito, Koji (The American Society for Cell Biology, 2012)
Tumor cells exhibit two interconvertible modes of cell motility referred to as mesenchymal and amoeboid migration. Mesenchymal mode is characterized by elongated morphology that requires high GTPase Rac activation, whereas amoeboid mode is dependent on actomyosin contractility induced by Rho/Rho-associated protein kinase (ROCK) signaling. While elongated morphology is driven by Rac-induced protrusion at the leading edge, how Rho/ROCK signaling controls amoeboid movement is not well understood. We identified FilGAP, a Rac GTPase-activating protein (GAP), as a mediator of Rho/ROCK-dependent amoeboid movement of carcinoma cells. We show that depletion of endogenous FilGAP in carcinoma cells induced highly elongated mesenchymal morphology. Conversely, forced expression of FilGAP induced a round/amoeboid morphology that requires Rho/ROCK-dependent phosphorylation of FilGAP. Moreover, depletion of FilGAP impaired breast cancer cell invasion through extracellular matrices and reduced tumor cell extravasation in vivo. Thus phosphorylation of FilGAP by ROCK appears to promote amoeboid morphology of carcinoma cells, and FilGAP contributes to tumor invasion.